(1)、等式右边=1/2[(a-b)^2+(b-c)^2+(c-a)^2]=1/2(a?-2ab+b?+a?-2ac+c?+b?-2bc+c?)=1/2(2a?+2b?+c?-2ab-2bc-2ac)=a?+b?+c?-ab-bc-ac=左边,故此等式正确.(2)、若a=2009,b=2010,c=2011,在(1)中,我们已经知道a^2+b^2+c^2-ab-bc-ac=1/2[(a-b)^2+(b-c)^2+(c-a)^2] 故把a=2009,b=2010,c=2011代入1/2[(a-b)^2+(b-c)^2+(c-a)^2] 中得:1/2[(2009-2010)^2+(2010-2011)^2+(2011-2010)^2]=1/2(1+1+4)=3故,若a=2009,b=2010,c=2011,a^2+b^2+c^2-ab-bc-ac的值为3(3)、在(1)中,我们已经知道a^2+b^2+c^2-ab-bc-ac=1/2[(a-b)^2+(b-c)^2+(c-a)^2] 而[(a-b)^2≥0、(b-c)^2≥0、(c-a)^2≥0要使当a=b=c时[(a-b)^2=(b-c)^2=(c-a)^2=0,也只有当a=b=c时,a^2+b^2+c^2-ab-bc-ac≤0.(此时只能取等,而≤是:“小于或等于”,因此是成立的)
a^2+b^2+c^2-ab-bc-ac=1/2[(a-b)^2+(b-c)^2+(c-a)^2]
2个回答
相关问题
-
计算(b-c)/(a2-ab-ac+bc)-(c-a)/(b2-bc-ac+ac)+(a-b)/(c2-ac-bc+ab
-
A=(b^2+c^2-a^2)/2bc,B=(a^2+c^2-b^2)/2ac,C=(a^2+b^2-c^2)/2ab
-
a+b+c=1,a^2+b^2+c^2=2,求ab+bc+ac
-
a^3+b^3+c^3-3ab=(a+b+c)(a^2+b^2+c^2-ab-ac-bc)=1/2(a+b+c)[(a-
-
(a+b+c)(a^2+b^2+c^2-ab-ac-bc)+3ab=
-
为什么ab+bc+ac)+a^2+b^2+c^2=(a+b+c)^2
-
已知a/(bc-a^2)+b/(ac-b^2)+c/(ab-c^2)=0,求a/(bc-a^2)^2+b/(ac-b^2
-
1.(a+b+c)(ab+bc+ac)-abc 2.2(a+b)(a+c)(b+c)+abc
-
a-b=2 b-c=3 求a^2+b^2+c^2-ab-bc-ac
-
数学CASE(a^2-ab-ac+bc)分之(2a-b-c)+(b^2-ac-bc+ac)分之(2b-c-a)+(c^2